EFFECT OF MONETARY POLICY ON THE PERFORMANCE OF LISTED DEPOSIT MONEY BANKS IN NIGERIA - GIMBA John Toro (Annals of the University of Oradea: Economic Science, 2020)
This study examines the effect of monetary policy on the performance of listed deposit money banks in Nigeria from 2006-2018. The research design adopted for this study was ex post-facto research design. Panel time series data were extracted based on the variables used in the study. Net profit margin (NPM) as the dependent variable, while liquidity ratio (LQR), Interest Rate (INR), Loan to deposit ratio (LDR) and cash reserve ratio (CRR) as independent proxies to measure monetary policy. The findings show that monetary policy has significant effect on the performance of listed deposit money banks in Nigeria. Based on the result, it was concluded that liquidity ratio and loan to deposit are significant on net profit margin, likewise interest rate and cash reserve ratio were insignificant on net profit margin. Therefore, the effect of monetary policy on the Nigeria commercial banks as an engine for controlling inflation, unemployment etc. is geared towards finding a positive and constructive role for the economy. Based on the findings, it was recommended that; the Central Bank of Nigeria should manage the monetary policy rate properly, with the recent increase of loan to deposit, Government should also employ other measures to control the loan to deposit and the monetary authorities should also minimize the 22.5 % Cash reserve ratio in order to influence the level of bank performance with capacity to raise a volume of funds and also reduce the liquidity ratio from 30% to 25% to prevent the banks from folding up.